Circadian rhythm genes mediate fenvalerate-induced inhibition of testosterone synthesis in mouse Leydig cells. Issue 23 (17th December 2017) - Guo, Yichen; Shen, Ouxi; Han, Jingjing; Duan, Hongyu; Yang, Siyuan; Zhu, Zhenghong; Tong, Jian; Zhang, Jie
ABSTRACT: Fenvalerate (Fen), a widely used pesticide, is known to impair male reproductive functions by mechanisms that remain to be elucidated. Recent studies indicated that circadian clock genes may play an important role in successful male reproduction. The aim of this study was to determine the effects of Fen on circadian clock genes involved in the biosynthesis of testosterone using TM3 cells derived from mouse Leydig cells. Data demonstrated that the circadian rhythm of testosterone synthesis in TM3 cells was disturbed following Fen treatment as evidenced by changes in the circadian rhythmicity of core clock genes (Bmal1, Rev-erbα, Rorα). Further, the observed altered rhythms were accompanied by increased intracellular Ca 2+ levels and modified steroidogenic acute regulatory (StAR) mRNA expression. Thus, data suggested that Fen inhibits testosterone synthesis via pathways involving intracellular Ca 2+ and clock genes (Bmal1, Rev-Erbα, Rorα) as well as StAR mRNA expression in TM3 cells.